Foreign direct investments (FDI) and economic growth: empirical evidence from Southern Africa Customs Union (SACU) countries - Suleiman, Najat Nassor; Kaliappan, Shivee Ranjanee; Ismail, Normaz Wana (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
Foreign direct investment (FDI) has been regarded as one of the important factors that stimulate the economic growth in most of the developing countries. However, fewer studies have explored the issue in the case of African region. This study examines the impact of FDI on economic growth for the Southern Africa Custom Union (SACU) countries namely; Botswana, Lesotho, Namibia, South Africa and Swaziland. Employing panel data from the period of 1980-2010 and using Dynamic Ordinary Least Squares (DOLS), the findings reveals satisfactory evidence that there is a positive and significant impact of FDI on the economic growth for the SACU countries.